Screening of Rhodomyrtus tomentosa (Aiton) Wight (Karamunting) Compounds that Have the Potential for Breast Cancer - Samsul Hadi; Kunti Nastiti (Hydrogen: Jurnal Kependidikan Kimia, 2023)
Breast cancer is the highest disease in the world beating lung cancer, so various alternatives are needed to find a treatment. Screening drug discovery against breast cancer by targeting BCL-2 occupies the main position and is the goal of this study. The method used is insilico. the material used is 10 compounds from R. tomentose, 2w3l protein from RCSB, PLANT docking software, the docking coordinate used is X: 39.8057 Y: 26.9355 Z: -12.4145 with a radius of 11.1871, then to find out the type of bond and residue involved using discovery studio. The results of this study were docking scores from -91.3871(5'-Desgalloylstachyurin) to -65.4754 (Afrormosin), activity predictions from PASS online from 0.174 (Rhodomyrtosone C) to 0.799 (Lupeol). Based on the docking score, three compounds that have the potential to inhibit the work of BCL-2 were obtained namely 5'-Desgalloylstachyurin, Rhodomyrtosone B and Rhodomyrtosone D.